Assessing inverse relationship in joint farm decision-making households: An empirical evidence from Eastern India - Malabayabas, Maria L.; Mishra, Ashok K. (Frontiers in Sustainable Food Systems, 2022)
In the eastern India region, due to the dominance of fragmented and smaller land holdings and lack of irrigation facilities, the adoption of green revolution technologies has progressed slowly. Economic growth, income, and land fragmentation have induced families to allocate labor to non-farm jobs. In the absence of male decision-makers, spouses are responsible for making farming-related decisions jointly with their husbands. This study examines the inverse relationship between farm size and rice productivity in joint farm decision-making among married couples. The study uses survey data from four eastern states of India. The finding confirms inverse relationship between cultivated rice area and rice yields. The inverse relationship holds but weakens when we control for farm and household characteristics and land quality. Smallholders in India tend to have dual employment, and as a result, more farm management decisions are being made jointly with spouses. Findings here indicate that joint farming decision-making may have an adverse effect on rice productivity. Socially advantaged farmers have a lower yield. Finally, the study reveals that off-farm income from off-farm employment increases rice productivity. Policymakers can strengthen extension services to disseminate farming knowledge (agronomic practices and technology) to socially disadvantaged farmers and off-farm job opportunities for smallholders.